La lingüística cognitiva y la lingüística aplicada a una ciencia para la comunicación transdisciplinar (2013)
ABSTRACT: In this work results of a qualitive hermeneutic research about a cognitive and applied linguistic related to other sciences in an specific context of a given scientific community were presented, a technical and scientific language regarding science and technology was pointed out from an integral vision in order to facilitate cognitive relationship among different disciplines. This study also allows to create capacities in order to assess vocabulary in context, useful for the transmission and transformation of knowledge according to a scientific method. The objective was directed to know about the relationship between the lexical unit and its meaning in a given communicative context and in the academic communication of a medical – legal forensic practice. The importance of educate during the teaching learning process is also mentioned in this research and the main objective is to develop an assertive medical practice among Psychopharmacology, psychiatric, anthropology and psychology with biomedical and human sciences.